Identity Dilemma and Self-Resilience: A Phenomenological Study of Students Working as Commercial Sex Workers - Arina Fathur Rohmah; Argo Widiharto; Agus Setiawan (Asosiasi Asesmen Pendidikan (AAP), 2025)
The phenomenon of students working while attending college is growing, including involvement in informal night work such as the entertainment industry and covert prostitution. The purpose of this study is to gain an in-depth understanding of how students who become commercial sex workers (CSWs) interpret their self-concept, as well as the social, economic, family, and psychological factors that shape this experience. The data analysis technique in this study uses a qualitative approach with the Interpretative Phenomenological Analysis (IPA) method, involving three female participants aged 22–25 who are active students and have experience working as “campus prostitutes”. The results show that involvement in this work is influenced by economic factors, broken home conditions, peer pressure, and the search for self-identity. The students experienced psychological conflicts in the form of guilt, moral dilemmas, efforts to maintain their identity, and strategies to balance their roles as students and night workers. Themes such as becoming a sex worker, time management, contraceptive use, worship, stigma, and economic change were recurring findings. This study confirms that informal night work has a significant impact on the formation of students' self-concept and psychosocial well-being.